(untitled) (Fiep Bulletin - online, 2011)
There is a consensus that education is the privileged way to promote the transformation of our society, to reduce social inequalities and promote improved quality of life. The ethical crisis of values, generated largely by the dominant development model, focused on competitiveness, consumerism and individualism, points to an urgent need for cultural change and values to build a more just and sustainable society. Considering that the sport has a great potential for development of values and taking advantage of the fact that Brazil will host two major sports mega-events, this study investigated how the sport can actually bring the legacy of values in education for adolescents, especially disadvantaged. It was conducted an exploratory study with 665 adolescents aged 11 to 14 years of public school, participants of mini volleyball competition of a social sportive Program from Instituto Compartilhar called Esporte Cidadão Unilever. Each participant should write on their badge value actions learned in the program that he practiced during the event: cooperation, respect, responsibility and autonomy. The quotes from students were tabulated and classified according to the value and category. The study showed a predominance of actions related to the values of cooperation and respect, demonstrating that these values can also be developed through sports and volleyball in a competitive situation.